Consumption Smoothing and Exchange Rate Volatility - Turtelboom, Bart (IMF Working Papers; Working Paper, 1995)
This paper analyzes exchange rate behavior in a model where consumers trade goods to diversify shocks to their income. A model with traded and nontraded goods is simulated in a multilateral context based upon historical output correlations for the period 1970-92. Simulation results indicate that the observed volatility of multilateral real exchange rates for the United States, Germany and Japan is not inconsistent with exchange rate volatility implied by consumption-smoothing behavior.